2007
DOI: 10.1159/000107563
|View full text |Cite
|
Sign up to set email alerts
|

Increased 12-Month Prevalence Rates of Mental Disorders in Patients with Chronic Somatic Diseases

Abstract: Background: Although it is well established that chronic somatic diseases are significantly associated with a wide range of psychopathology, it remains unclear to what extent subjects with chronic somatic diseases are at increased risk of experiencing mental disorders. The present epidemiological study investigates age- and sex-adjusted 12-month prevalence rates of mental disorders in patients with cancer, and musculoskeletal, cardiovascular and respiratory tract diseases, based on comprehensive physicians’ di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
103
0
22

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 209 publications
(133 citation statements)
references
References 70 publications
8
103
0
22
Order By: Relevance
“…Another explanation for these increased costs could be that patients with diabetes and comorbid mental disorders have a more severe somatic disease status, which in turn would result in more frequent healthcare utilisation and higher healthcare costs. This hypothesis is supported by previous findings highlighting the association between the severity of diseases and the presence of comorbid mental disorders [51][52][53]. However, a significant effect of mental disorders on healthcare costs was found in primary studies that had adjusted for medical comorbidities or diabetes complications [9, 14, 19, 20, 25, 26, 29-31, 34, 35, 39, 41, 42, 46, 47].…”
Section: Discussionsupporting
confidence: 83%
“…Another explanation for these increased costs could be that patients with diabetes and comorbid mental disorders have a more severe somatic disease status, which in turn would result in more frequent healthcare utilisation and higher healthcare costs. This hypothesis is supported by previous findings highlighting the association between the severity of diseases and the presence of comorbid mental disorders [51][52][53]. However, a significant effect of mental disorders on healthcare costs was found in primary studies that had adjusted for medical comorbidities or diabetes complications [9, 14, 19, 20, 25, 26, 29-31, 34, 35, 39, 41, 42, 46, 47].…”
Section: Discussionsupporting
confidence: 83%
“…Current mental health policy in the UK emphasises the notion of recovery (Department of Health, 2014), reinforcing a short-term view about common mental health problems in primary care. Our findings align with the extant literature (Burcusa & Iacono, 2007;Yiend et al, 2009;Harter et al, 2007;Hardeveld et al, 2010;Gopinath et al, 2007) and suggest taking the long view, recognising that 19 problems like depression often have to be managed like recurrent long-term conditions.In this regard, we would recommend two areas for future practice developments. First, the influence of residual depression symptoms on the risk of relapse is well documented (Vittengl et al, 2007;Paykel et al, 1995), and it is known that around 76% of such cases relapse within 10 months of treatment completion (Paykel, 2008).…”
supporting
confidence: 90%
“…1 It is now well-established that particular cohorts of patients with chronic medical illness have a much greater prevalence of affective disorders than the general population. 2 Furthermore, it has been demonstrated that these patients experience worse health outcomes -including a reduced quality of life and increased mortality -compared to matched patients without depression. 3,4 Recent studies suggest that the scale and impact of depression in patients with CLD or OLT is comparable to that of other chronic medical diseases, and that these adverse effects may be reduced through the optimal use of antidepressants.…”
Section: Discussionmentioning
confidence: 99%